REPUTASI KESUSASTRAAN MELAYU DALAM PENDIDIKAN DAN BUDAYA GLOBAL (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
The Malay nation has a very long history in the archipelago. Starting from the language that received the title of lingua franca, script, culture, to producing literature that contains cultural values that are so deep. Thus, the Malay language and its works are one of the cultural treasures of the archipelago. This study uses literature study method. The results of the study show that along with the development of the times, Malay literature is considered to have experienced a degradation of existence. This literature met a turning point and its reputation faded to be replaced by modern literature such as poetry and romance. Basically this happens not because of the literary entity, but because the next author or writer cannot give life or soul to every literature. One way to continue to revive and preserve Malay culture is through education in formal institutions. Unfortunately, in the current national education curriculum, the teaching of classical Malay literature is minimized. This makes the reputation of Malay literature dim and raises concerns about the loss of Malay culture in the archipelago.